Synchronizing between Lasswell’s Communication Model and Abram’s Critical Orientation as a Sophisticated Concept of Literary Communication and Its Associated Studies - Sarif Syamsu Rizal (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
Abstract. This scientific article is entitled "Synchronizing between Lasswell's Communication Model and Abrams' Critical Orientation as a Sophisticated Concept of Literary Communication and Its Associated Studies". By using a multidisciplinary study, one study in solving a problem using various points of view of many relevant sciences in this case, such as literature and communication science, the research question of this article is synchronizing between Lasswell’s Communication Model and Abrams' Critical Orientation as a Sophisticated Concept of Literary Communication and Its Associated Studies. The literature review used as a scientific foundation in conducting this theoretical review, among others, is Nature of Literature and Literary Works, Sigmund Freud’s Psychoanalytic: Mind Structure and Topography, Intertextuality Act, Mayer Howard Abrams’ Critical Orientation, and Harold Dwight Lasswell’s Communication Model. The design of this article represents a theoretical review of a comparative study between communication science and literary studies. The technique of data analysis used is Lasswell's model to describe components of literary communication and its associated studies. The results of this article are the components of literary communication consisting of the source as the ideas, the artist as the communicator, the main idea in literary work as the message, the figurative language as media, and the audience as the receiver, and impact as the effect. The studies of each component are that mimetic, expressive, objective, and pragmatic studies.Keywords: communication, component, model, studies, synchronizingAbstrak. Artikel ilmiah ini berjudul "Sinkronisasi antara Model Komunikasi Lasswell dan Orientasi Kritis Abrams sebagai Konsep Canggih Komunikasi Sastra dan Studi Terkait". Dengan menggunakan studi multidisiplin, satu studi dalam memecahkan masalah menggunakan berbagai sudut pandang banyak ilmu yang relevan dalam kasus ini, seperti sastra dan ilmu komunikasi, pertanyaan penelitian dari artikel ini adalah sinkronisasi antara Model Komunikasi Lasswell dan Orientasi Kritis Abrams sebagai Konsep Canggih Komunikasi Sastra dan Studi Terkait. Tinjauan literatur yang digunakan sebagai landasan ilmiah dalam melakukan tinjauan teoretis ini, antara lain adalah Sifat Karya Sastra dan Sastra, Psikoanalitik Sigmund Freud: Struktur dan Topografi Pikiran, Tindakan Antartekstualitas, Orientasi Kritis Mayer Howard Abrams, dan Model Komunikasi Harold Dwight Lasswell . Desain artikel ini merupakan tinjauan teoritis studi banding antara ilmu komunikasi dan studi sastra. Teknik analisis data yang digunakan adalah model Lasswell untuk menggambarkan komponen komunikasi sastra dan studi terkaitnya. Hasil dari artikel ini adalah komponen komunikasi sastra yang terdiri dari sumber sebagai ide, artis sebagai komunikator, ide utama dalam karya sastra sebagai pesan, bahasa kiasan sebagai media, dan audiens sebagai penerima, dan dampak sebagai efek. Studi masing-masing komponen adalah studi mimesis, ekspresif, objektif, dan pragmatis.Kata kunci: komunikasi, komponen, model, studi, sinkronisasi